Diagnostic therapeutic care pathway for pediatric food allergies and intolerances in Italy: a joint position paper by the Italian Society for Pediatric Gastroenterology Hepatology and Nutrition (SIGENP) and the Italian Society for Pediatric Allergy and Immunology (SIAIP) - Roberto Berni Canani; Carlo Caffarelli; Mauro Calvani; Alberto Martelli; Laura Carucci; Tommaso Cozzolino; Patrizia Alvisi; Carlo Agostoni; Paolo Lionetti; Gian Luigi Marseglia (BMC, 2022)
Abstract Epidemiologic data suggest an increased prevalence of pediatric food allergies and intolerances (FAIs) during the last decades. This changing scenario has led to an increase in the overall healthcare costs, due to a growing demand for diagnostic and treatment services. There is the need to establish Evidence-based practices for diagnostic and therapeutic intervention that could  be adopted in the context of public health policies for FAIs are needed. This joint position paper has been prepared by a group of experts in pediatric gastroenterology, allergy and nutrition from the Italian Society for Pediatric Gastroenterology Hepatology and Nutrition (SIGENP) and the Italian Society for Pediatric Allergy and Immunology (SIAIP). The paper is focused on the Diagnostic Therapeutic Care Pathway (DTCP) for pediatric FAIs in Italy.